Upaya Konservasi Waduk Selorejo Berdasarkan Perkembangan Peta Penggunaan Lahan Dalam Kurun Waktu Tahun 2000–2011 - Yudiarso, Rendra Arif; Suhartanto, Ery; Soetopo, Widandi (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2014)
Selorejo Reservoir is managed by the Perum Jasatirta I. Selorejo reservoir was planned for 50 years in effective usage. By the end year of 2010 this reservoir has been operated for 38 years. This study was conducted to determine the amount of sediment inflow into the reservoir, how many year the effective usage of Selorejo reservoir is still remain, and the conservation efforts are made to maintain the effective usage of the reservoir. The Estimation of erosion rates is calculated by the AVSWAT 2000’s model approach and calculate the Reservoir’s effective by the Linsley empirical equation. With the Brunne efficiency trap method obtained the rest of reservoir effective usage is about 10.99 years ( from 12 years rest of the Reservoir effective usage). Another empirical approach with the Churchill efficiency trap method obtained the rest of reservoir effective usage is about 17.66 years. Based on the Brunne efficiency trap method calculation, the Reservoir effective usage can not reached. short-term Reservoir conservation effort can reduce the sediment about 85.55 % each year with 5.05 billion in cost, the medium term can reduce the sediment about 4:03 % each year with 12.2 billion in implementation and OM cost, and the long-term can reduce the sediment 63.9 % each year. Based on the percentage of sediment reduction, the budget plan costs, and the direct benefits that can be perceived, so the short-term alternative can be used as the priority for reservoir management.Keywords: AVSWAT 2000, Reservoir’s effective time, Conservation.